Tradimenti: un rischio necessario - Santoni, Irene (SocietàMutamentoPolitica, 2012)
The argument of this critical note is betrayal in the relationships from a sociological point of view. In this perspective, the action of betray seems like one of the ways to interact; each person take this risk living a relationship. By the reading of literature concerning the different conceptions of betrayals, I will analyse the phenomenology of this phenomenon many-sided and ordinary at the same time. In betrayals the part of the betrayer and the betrayed are faint.